Studi Kasus Asuhan Keperawatan pada Orang Dewasa dengan Ca Ovarium: Nursing Care for Adults with Ovarian Cancer - Dwi Novitasari; Eka Yuliana (Journal of Nursing Education and Practice, 2022)
Introduction:Ovarian cancer is very common in women and in its early stages usually does not cause complaints. Complaints will only be felt when they have entered stage II to stage IV where the patient will begin to feel pain, anemia, ascites until anorexia occurs. Pain felt in patients with ovarian cancer is usually chronic, acute to chronic and intermittent. This condition is based on the stage of cancer experienced. Objectives:This study aims to describe nursing care and approriate intervention in ovarium cancer patient who experience pain. Method: This research is a case study design using simple random sampling technique for sampling. This research was conducted in December 2020 with an assessment guide instrument for data collection. Researchers use the nursing care process from the assessment stage to evaluation. Result: The complaint that most felt and disturbed the patient was pain around the surgical area that radiated to the back on a scale of 5, the pain was intermittent and felt like being stabbed. Pain will be felt when the patient moves. The provision of deep breathing therapy interventions carried out for a period of 3 days has not been able to reduce the scale of pain felt in post-operative ovarian cancer patients. Conclution: Pain management measures show that they have not been able to change the pain scale they feel, so they can continue until the pain scale shows a decrease. Nurses can apply and modify alternative uses of other non-pharmacological therapies in reducing pain in addition to deep breathing relaxation techniques.